ChemInform Abstract: Total Synthesis and Biological Evaluation of Jerantinine E. Issue 21 (27th May 2014) - Frei, Reto; Staedler, Davide; Raja, Aruna; Franke, Raimo; Sasse, Florenz; Gerber‐Lemaire, Sandrine; Waser, Jerome
Abstract The first total synthesis of the target compound in 17 steps and 16% overall yield is reported.